Kehujjahan Hadis Mursal Menurut Imam Madzhab Empat - Abidin, Achmad Azis (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2020)
According to the muhaddits, a hadis is acceptable and reliable to be hujjah in law when its sanad has continuous authority till the Prophet Muhammad, beside that the narrator who delivered it is a tsiqat (‘adil and dhabt). If some sanads are ommited between the successor and the Prophet Muhammad, the hadis is called mursal. Islam scholars have different views in measuring the credibility and realibility of mursal hadis. Some of them absolutely received mursal hadis to be hujjah, the other one received it by giving requisites, while the rest of scholars absolutely rejected it. This article presented the opinion of four Islamic legal schools (Imam Abu Hanifah (d. 148 H), Imam Malik bin Anas (d. 179 H), Imam Syafi’i (d. 204 H), and Imam Ahmad bin Hanbal (d. 241 H)) regarding the validity of mursal hadis as hujjah. This result of this arcticle revealed that Imam Abu Hanifah, Imam Malik bin Anas, and Imam Ahmad bin Hanbal accepted mursal hadis as hujjah by generally requites. Furthermore, Imam Syafi’i accepted it by specially requites.